Cell Senescence and the DNA Single-Strand Break Damage Repair Pathway - Parvathy A. Sarma; Corinne Abbadie; Yvan de Launoit; Fabrizio Cleri (DNA)
Cellular senescence is a response to endogenous and exogenous stresses, including telomere dysfunction, oncogene activation, and persistent DNA damage. In particular, radiation damage induces oxidative base damage and bond breaking in the DNA double-helix structure, which are treated by dedicated enzymatic repair pathways. In this review, we discuss the correlation between senescence and the accumulation of non-repaired single-strand breaks, as can occur during radiation therapy treatments. Recent in vitro cell irradiation experiments using high-energy photons have shown that single-strand breaks may be preferentially produced at the borders of the irradiated region, inducing senescence in competition with the apoptosis end-point typically induced by double-strand breaks. Such a particular response to radiation damage has been proposed as a possible cause of radiation-induced second primary cancer, as cells with an accumulation of non-repaired single-strand breaks might evade the senescent state at much later times. In addition, we highlight the peculiarities of strand-break repair pathways in relation to the base-excision pathway that repairs several different DNA oxidation defects.